2020
DOI: 10.1016/j.jcbs.2020.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Modeling suicide risk among parents during the COVID-19 pandemic: Psychological inflexibility exacerbates the impact of COVID-19 stressors on interpersonal risk factors for suicide

Abstract: Public health researchers have raised the concern that both the 2019 coronavirus disease (COVID-19) pandemic and the ensuing public health response will increase interpersonal stressors associated with suicide risk. The Acceptance and Commitment Therapy (ACT) framework conceptualizes psychological flexibility as an important way to reduce the impact of painful and even catastrophic events on psychological suffering. The current study examines psychological flexibility as a potential moderator of the prevailing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
42
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 37 publications
6
42
0
11
Order By: Relevance
“…In a study in Italy, 51 PF processes including cognitive defusion, self-as-context, values and committed action were found to moderate the relations between lockdown risk factors and mental health. It was also observed that psychological inflexibility moderated the association between COVID-19 stressors and suicide risks, 13 and the association between social isolation and mental health. 59 Further longitudinal studies including moderation and mediation analysis are needed to understand the PF as a potential mechanism for reducing the impact of the pandemic on people with chronic pain.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a study in Italy, 51 PF processes including cognitive defusion, self-as-context, values and committed action were found to moderate the relations between lockdown risk factors and mental health. It was also observed that psychological inflexibility moderated the association between COVID-19 stressors and suicide risks, 13 and the association between social isolation and mental health. 59 Further longitudinal studies including moderation and mediation analysis are needed to understand the PF as a potential mechanism for reducing the impact of the pandemic on people with chronic pain.…”
Section: Discussionmentioning
confidence: 95%
“…In a study investigating the impact of lockdowns on mental health in Italy, 51 it was found that PF processes, including cognitive defusion, self-as-context, values, and committed action, moderated the impact of lockdown risk factors on COVID-19 peritraumatic distress (distress due to COVID-19 lockdown), general anxiety, and depression. Psychological inflexibility was also found to moderate the association between COVID-19 stressors and suicide risks among parents, 13 as well as the association between social isolation and mental health in the general population. 59 There is also supporting evidence for the association between PF and anxiety disorders.…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, several recent studies conducted in Italy [ 37 ], the United Kingdom [ 38 , 39 ], the United States [ 40 , 41 , 42 ], and Poland [ 43 ] have indicated how the facets of psychological flexibility play an important role in mitigating the impacts of the COVID-19 pandemic on mental health [ 37 , 38 , 39 , 40 , 41 , 43 , 44 ]. Of the aforementioned studies, some have further shown that the opposite processes of psychological flexibility, that is, the psychological inflexibility or experiential avoidance were positively associated with parenting stress and family discord [ 44 ], and moderated the suicidal risk in the context of COVID-19 stressors such as resource constraints and loss arising from the pandemic [ 42 ]. In literature, psychological flexibility has been regarded as a typical model of clinical psychological treatment, comprising the psychological processes related to acceptance, mindfulness and committed actions based on values [ 16 , 32 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although some parents mobilize coping and resilience strategies in the face of the COVID-19 threats [1,2], some are at risk of experiencing worsened mental health problems or developing new stress-related disorders [3,4]. The initial evidence obtained indicating how the ongoing pandemic has negatively affected the health and well-being of parents and children [4][5][6][7][8][9][10] probably barely scratches the surface of the potential long-term effects of the pandemic on families' health and well-being. These problems may continue even after the pandemic has abated and the distancing measures have been lifted due to self-sustaining processes.…”
Section: Introductionmentioning
confidence: 99%